2003
DOI: 10.1080/11024159850191067
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic T2-sympathetic block by clipping-a better and reversible operation for treatment of hyperhidrosis palmaris: experience with 326 cases

Abstract: Forced air warming intraoperatively can preserve normothermia during extensive thoracoabdominal operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
149
2
10

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(166 citation statements)
references
References 0 publications
5
149
2
10
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18][19][20][21][22] This access route, after the surgeon has acquired adequate experience through training in videoassisted thoracoscopy, allows well-directed surgery to be performed, with minimal risk of the disagreeable complications that occurred in the past when the transcervical route was used, as well as the sequelae and scars of classical thoracotomy. [23][24][25][26] In using the transcervical route, injury to the stellate ganglion is in fact very frequent and expected, producing significant sequelae: the so-called Claude-Bernard-Horner syndrome (palpebral ptosis, miosis and enophthalmos).…”
Section: Total 743mentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15][16][17][18][19][20][21][22] This access route, after the surgeon has acquired adequate experience through training in videoassisted thoracoscopy, allows well-directed surgery to be performed, with minimal risk of the disagreeable complications that occurred in the past when the transcervical route was used, as well as the sequelae and scars of classical thoracotomy. [23][24][25][26] In using the transcervical route, injury to the stellate ganglion is in fact very frequent and expected, producing significant sequelae: the so-called Claude-Bernard-Horner syndrome (palpebral ptosis, miosis and enophthalmos).…”
Section: Total 743mentioning
confidence: 99%
“…In some centers, the surgery is performed using two punctures through which a 2-mm scope and the tip of a cauterizer are introduced with the objective of selectively destroying the second thoracic ganglion (T 2 ). 10,12,[14][15][16][18][19][20] For this strategy, CO 2 insufflation is required in order to deviate the lung. The scar so produced is minimal and the procedure is esthetically excellent, with a scar the size of a percutaneous puncture (needlescopic sympathectomy).…”
Section: Total 743mentioning
confidence: 99%
“…7) In 2001, Lin and Wu first reported a significant reduction in compensatory sweating when T4 thoracic sympathicotomy was employed to treat palmar hyperhidrosis. 8) Several studies later confirmed that T4 sympathicotomy avoided compensatory sweating, patients were highly satisfied, and that this approach was preferred in the treatment of palmar hyperhidrosis. [1][2][3][4]9) In some patients, however, improvement in palmar sweating was less defined and its efficacy was incomplete.…”
Section: Discussionmentioning
confidence: 91%
“…There are several observational studies on the effect of clamping of the sympathetic chest chain 3,4,7,10,11 . They show block conduction but without showing the histological lesion.…”
Section: Assessment Of Inflammation and Necrosismentioning
confidence: 99%
“…Several series were published for the treatment of hyperhidrosis of the upper limb [3][4][5][6][7][8][9][10][11] . One of the problems encountered in all surgical techniques was the individuality, tending to justify the side effects by saying: "it seems to work on my hands" 12 .…”
Section: Introductionmentioning
confidence: 99%